2020
DOI: 10.3390/cancers12020300
|View full text |Cite
|
Sign up to set email alerts
|

EVI1 as a Prognostic and Predictive Biomarker of Clear Cell Renal Cell Carcinoma

Abstract: The transcription factor EVI1 plays an oncogenic role in several types of neoplasms by promoting aggressive cancer features. EVI1 contributes to epigenetic regulation and transcriptional control, and its overexpression has been associated with enhanced PI3K-AKT-mTOR signaling in some settings. These observations raise the possibility that EVI1 influences the prognosis and everolimus-based therapy outcome of clear cell renal cell carcinoma (ccRCC). Here, gene expression and protein immunohistochemical studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The expression of ATP1A1-AS1 decreased in the more advanced T-stages, while the expression levels of IL10RB-DT and MELTF-AS1 were enhanced more novel options and prolonged survival of plenty of patients with ccRCC, the curative effects of another part of patients remain unsatisfactory [2,6,19]. Multiplied studies revealed the individual variation at the genetic level should be responsible for the phenomenon [20,21]. Therefore, more explorations and understanding of ccRCC characterized by variant molecular heterogeneous, and further identifying more sensitive and effective immune prognostic indicators are above rubies.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ATP1A1-AS1 decreased in the more advanced T-stages, while the expression levels of IL10RB-DT and MELTF-AS1 were enhanced more novel options and prolonged survival of plenty of patients with ccRCC, the curative effects of another part of patients remain unsatisfactory [2,6,19]. Multiplied studies revealed the individual variation at the genetic level should be responsible for the phenomenon [20,21]. Therefore, more explorations and understanding of ccRCC characterized by variant molecular heterogeneous, and further identifying more sensitive and effective immune prognostic indicators are above rubies.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,19 Multiplied studies revealed the individual variation at the genetic level should be responsible for the phenomenon. 20,21 Therefore, more explorations and understanding of ccRCC characterized by variant molecular heterogeneous, and further identifying more sensitive and effective immune prognostic indicators are above rubies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that these genes are all related to prognosis in different cancer type. [35][36][37] No significant kinase was found to be enriched. In essence, these findings suggested that MMP28 is tightly connected to prognosis and survival of PAAD patients.…”
Section: Underlying Regulators Of Mmp28-correlated Genes In Paadmentioning
confidence: 96%